Beberapa aspek hukum perjanjian jual belt barang dengan mempergunakan kartu kredit dan perkembangan penggunaannya di Medan=Some Legal Aspects on the Sales of Goods Using Credit Card - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Recently, using credit card in the sales of goods agreement has been developed very fast, especially after Kepres (Decision of President) No. 61/1988 and KepMenKeu RI (Decision of Minister of Finance Affairs) No. 1251/EMIC-013/1988. But detailed regulations which govern the mechanism of using it has not been found Due to this fact, the problem arises on the characteristic of the CO10 of goods agreement which uses the credit card in the transaction and the principles in applying it A descriptive analytical approach for the research was conducted by using a questionnaire, an interview and a checklist as research instruments. Sample for this study determined by purposive random sampling method Result of this research showed that credit card was not a medium of exchange in general meaning, but in a method to pay quaranted by card issuer through official .documents. Sales of goods using the credit card agreement was a mixed (suigeneris), derivative and implied in-law agreement. The card issuer got the position higher than another parties. Although card issuer did not want to be involved with the two another relationship, but they took merchant's side rather than cardholder's side and the cardholder was in the weak position. Credit card cases in court have been dominated by credit card crime rather than tort ones, because they arranges out of court.